2021
DOI: 10.1186/s13030-021-00228-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of the gut microbiota in the pathogenesis of anorexia nervosa

Abstract: Anorexia nervosa (AN), an eating disorder, is characterized by extreme weight loss and fear of weight gain. Psychosocial factors are thought to play important roles in the development and progression of AN; however, biological factors also presumably contribute to eating disorders. Recent evidence has shown that the gut microbiota plays an important role in pathogenesis of neuropsychiatric disorders including AN. In this article, we describe the possible role of the gut microbiota in the development and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 93 publications
(108 reference statements)
0
9
1
Order By: Relevance
“…The gut microbiome has captured the attention of the medical field and has been implicated in a myriad of conditions including neuropsychiatric disorders, encompassing eating disorders (EDs) [1], metabolic disorders, and immune-mediated diseases. Research regarding EDs and the gut microbiome remains nascent and speculative, yet promising [2][3][4][5][6][7][8][9]. Here we provide a critical analysis of the field, suggest practical steps that can be taken to move the field forward, and discuss the potential implications of this research.…”
Section: Overviewmentioning
confidence: 99%
“…The gut microbiome has captured the attention of the medical field and has been implicated in a myriad of conditions including neuropsychiatric disorders, encompassing eating disorders (EDs) [1], metabolic disorders, and immune-mediated diseases. Research regarding EDs and the gut microbiome remains nascent and speculative, yet promising [2][3][4][5][6][7][8][9]. Here we provide a critical analysis of the field, suggest practical steps that can be taken to move the field forward, and discuss the potential implications of this research.…”
Section: Overviewmentioning
confidence: 99%
“…Therefore, dietary reduction, psychosocial stress, and marked weight loss are considered to contribute to the establishment of a selective intestinal environment for bacterial survival favouring the development of dysbiosis [ 19 ]. So far, it has been suggested that this might explain low weight gain [ 19 , 22 ], affective symptomatology [ 19 , 22 , 23 ], altered eating behaviour [ 23 ], and even hyperactivity [ 22 ]. Thus, modifications of microbiota composition using pro-, prebiotics [ 22 ], FMT, or precision nutrition [ 19 ] have been proposed as promising therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it has been suggested that this might explain low weight gain [ 19 , 22 ], affective symptomatology [ 19 , 22 , 23 ], altered eating behaviour [ 23 ], and even hyperactivity [ 22 ]. Thus, modifications of microbiota composition using pro-, prebiotics [ 22 ], FMT, or precision nutrition [ 19 ] have been proposed as promising therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations